Bringing States to Justice for Crimes against Humanity: The Compromissory Clause in the International Law Commission Draft Convention on Crimes against Humanity. (22nd October 2018) - Zimmermann, Andreas; Boos, Felix
Abstract: Draft Article 15 of the International Law Commission's project on crimes against humanity — dealing with the settlement of disputes arising from a proposed convention — attempts to strike a balance between state autonomy and robust judicial supervision. It largely follows Article 22 of the Convention on the Elimination of All Forms of Racial Discrimination, which renders the jurisdiction of the International Court of Justice (ICJ) conditional upon prior negotiations. Hence, the substance of the clause can be interpreted in light of the recent case law of the ICJ, especially in the case Georgia v. Russia . In addition, this contribution discusses several issues regarding the scope ratione temporis of the compromissory clause. It advances several proposals to improve the current draft, addressing its relationship with state responsibility — an explicit reference to which is currently missing — as well as the relationship between the ICJ and a possible treaty body. It also proposes to recalibrate the interplay of the requirement of prior negotiations with, respectively, the possibility of seizing a future treaty body and the indication of provisional measures by the ICJ.